ANALISIS PENGARUH KINERJA KEUANGAN, BI RATE DAN EARNING PER SHARE TERHADAP HARGA SAHAM BANK BUMN DI BURSA EFEK INDONESIA (PERIODE 2008-2013) - Selamet Riyadi (Akademi Akuntansi YKPN Yogyakarta, 2014)
This study aims to analyze the influence of variable financial performance, the BI rate and EPS to state-owned bank's stock price. The results of this study are expected to provide information for the management of state-owned banks as consideration making the right decisions for the progress of the red plate banks and investors. The object is a state-owned bank that listing in Indonesia Stock Exchange (IDX) 2008-2013. The sample used is judgment sampling method with the state-owned bank criteria. Based on these criteria, the sample was obtained 4. The data were processed using Eviews Program version 6.0. The analytical tool used is panel data regression method using hypothesis testing, ie the T test, F test, test. The results of this study indicate that partial, LDR has a positive but not significant effect on stock prices, CAR has a positive and significant impact on stock prices, NIM positive and not significant to the stock price, the BI rate has positive effect on stock prices and EPS positive effect significant impact on stock prices. LDR independent variables simultaneously, CAR, NIM, the BI rate and EPS have a significant effect on stock prices. The results of the determination coefficient test showed 89.17 percent of the value of the dependent variable is affected by the independent variable, and the remaining 10.83 percent is influenced by other variables outside of research. Banks that maintain the soundness of banks in accordance with the method Risk Base Bank Rating (RBBR) set by Bank Indonesia to maintain its stock price in Indonesia Stock Exchange (IDX). For the investor in CAR and EPS can be used as a reference to set the options for the investment and management of the bank should maintain CAR and EPS increase continuously. Keywords: Financial Performance, BI rate, EPS, and stock price.